A critical Response to “How firearm legislation impacts firearm mortality”, A focused look at Canadian and Australian evidence - Caillin Langmann (Health Policy Open)
A recent review article in Health Policy Open, entitled “How firearm legislation impacts firearm mortality internationally: A scoping review” claims that Australian and Canadian firearms legislation is associated with reductions in homicide and suicide by firearms. Unfortunately, the review overexaggerates the effectiveness of firearms legislation in Australia and Canada, leaves out some important studies, and does not rigorously examine these articles.Eight Australian studies are referenced that examine the association between gun control legislation, primarily the National Firearms Act (NFA), and firearm homicide. Seven studies find no association between gun control legislation and firearm homicide. Only one study finds a reduction in female homicide but this is contradicted by a study using methods controlling for confounding factors. Four studies examining suicide rates and the association with the NFA find no associated benefit, including the single study that controls for confounders. Two studies find an associated decline in firearm suicide rates with the NFA but there is a decline in non firearms homicide rates at the same time that makes it impossible to know if the decline is associated with the NFA or another variable.The results of the Canadian studies on legislation and the association with firearms homicide points to no beneficial association when more methodologically sound methods and studies are reviewed. Canadian studies on the association with legislation and suicide by firearm demonstrate a reduction in suicide rates with a substitution for other methods and no overall reduction in suicide rates.Overall, Australian and Canadian studies to not appear to demonstrate beneficial associations with gun control legislation.